Effects of Mn substitution on crystal structure, magnetic and magnetocaloric properties of (Co1−xMnx)2B compounds. (20th October 2017) - Wang, D; Ma, L; Rao, G H; Wang, J; Zhang, X; Guo, Y B; Li, L
Abstract: The crystal structure, magnetic and magnetocaloric properties of (Co1− x Mn x )2 B ( x   =  0.0, 0.1, 0.2, 0.25, 0.3, 0.35, 0.40) compounds were investigated by x-ray powder diffraction (XRD) and magnetization measurements. All compounds crystallize in a body-centred tetragonal single phase with the CuAl2 -type structure. Due to the changes of lattice stability and ferromagnetic–antiferromagnetic exchange coupling interaction, the room temperature magnetization and the Curie temperature ( T C ) of (Co1− x Mn x )2 B compounds first increases at about x   =  0.1 and then decreases with the substitution of Mn for Co. Second-order phase transition was confirmed based on the isothermal magnetization curves and the isothermal entropy change (Δ S M ) was determined for the samples with x   =  0.3, 0.35 and 0.4. The maximal magnetic entropy (|Δ S M |) under a field change from 0 to 5 T are found to be 2.49, 2.37 and 2.02 J kg −1 ·K for x   =  0.3, 0.35 and 0.4, respectively. The corresponding relative cooling powers (RCP) are evaluated to be 59.74, 78.94 and 113.50 J kg −1 . Given the low cost of Co, Mn and B, (Co1− x Mn x )2 B compounds may come as an base compound for a more efficient magnetocaloric material.